1999
DOI: 10.1055/s-1999-243
|View full text |Cite
|
Sign up to set email alerts
|

Niedrigdosis Dental-CT

Abstract: A considerable dose reduction without loss of diagnostic information is achievable in dental CT. Dose-reducing examination protocols like the one presented may further expand the use of preoperative dental CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…Dose values of this study are in good correlation to data found in other studies [3,6,7,8,9]. Lowering the milliamperage product and increasing pitch may lead to a dose reduction by factor 9 in CT without any loss of diagnostic information [7].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Dose values of this study are in good correlation to data found in other studies [3,6,7,8,9]. Lowering the milliamperage product and increasing pitch may lead to a dose reduction by factor 9 in CT without any loss of diagnostic information [7].…”
Section: Discussionsupporting
confidence: 87%
“…Lowering the milliamperage product and increasing pitch may lead to a dose reduction by factor 9 in CT without any loss of diagnostic information [7]. In another study, a dose reduction of 75 % did not lead to a reduced metric accuracy [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The axial plane was the least precise in affording resorption identification, followed by the coronal and the sagittal planes. As demonstrate elsewhere 11 , clinicians must know the best protocol to resort for an accurate diagnosis when requesting CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…Entsprechend dem gegenwärtigen Standard der präoperativen Dokumentation werden bei allen Patienten präoperativ ein OPG, eine Aufnahme nach Clementschitsch sowie bei bilateralen Hypoplasien ein Fernrönt-genseitbild angefertigt [8]. Nur in besonderen Fällen ist eine erweiterte radiologische Diagnostik (CT) indiziert [13,14].…”
Section: Diskussionunclassified